Structure and labor use pattern among cocoa farmers in Ondo State, Nigeria - Oladokun, Yetunde Olasimbo Mary; OLUYOLE, kayode AKANNI; Oladipo, Akinpelu Ayodele (Indonesian Coffee and Cocoa Research Institute, 2023)
Human labour is about the only main source of labour available to smallholder farmers in Nigeria. Smallholder farmers contribute over 85% of domestic agricultural output in Nigeria, hence, human labour accounts for the domestic food supply in Nigeria. Therefore, the need to continue supplying food for the ever-growing Nigerian population anchors on human labour productivity. In Nigerian agriculture, hired labour is predominantly used. Human labour plays a very significant role in agricultural development, especially in developing countries where technological development is still very low. In view of the importance of labour in agricultural production, this study was designed to investigate the structure and use pattern of farm labour in the study area. The study was carried out in Ondo state, Nigeria. A multistage sampling technique was used to collect data from 160 farmers. After sorting for missing data, 144 cocoa farmers’ data were used for analysis in this study. Seventy-five percent of the total respondents were above 50 years of age and about 25.01% of the total respondents were 50 years and below. The majority (79.17%) of the farmers were men. Also, 75.07% of the respondents had a formal level of education. In the study contract type of labour is majorly used for most activities in cocoa farming while cooperative labour was seldom used. Activities such as land clearing (75.0%), planting (83.32%), weeding (95.83%), application of chemicals (91.67%), removal of mistletoes (87.50%), harvesting of cocoa pods (87.50%), conveyance of cocoa pods to the pod breaking point (95.83%), breaking of cocoa pods (100%) and conveyance of cocoa beans to the point of fermentation (88.33%) were majorly carried out by contract labour. Male labour was mostly utilized for all the activities as indicated by most farmers. Female labour was sparingly utilized for some activities such as land clearing (8.33%), planting (0%), application of chemicals (8.33%), spraying of chemicals (4.17%), removal of mistletoes (0%) and harvesting of cocoa pods (12.5%). The study recommended that funds should be made available to farmers to engage in contract labour and also there should be the need to use equipment and machinery to reduce drudgery.